Co-cultured spheroids of human periodontal ligament mesenchymal stem cells and vascular endothelial cells enhance periodontal tissue regeneration - Sano, Kotaro (Regen Ther, 2020)
INTRODUCTION: Human periodontal ligament mesenchymal stem cells (hPDLMSCs) have been known that they play important roles in homeostasis and regeneration of periodontal tissues. Additionally, spheroids are superior to monolayer-cultured cells. We investigated the characteristics and potential of periodontal tissue regeneration in co-cultured spheroids of hPDLMSCs and human umbilical vein endothelial cells (HUVECs) in vitro and in vivo. METHODS: Co-cultured spheroids were prepared with cell ratios of hPDLMSCs: HUVECs = 1:1, 1:2, and 2:1, using microwell chips. Real-time polymerase chain reaction (PCR) analysis, Enzyme-Linked Immuno Sorbent Assay (ELISA), and nodule formation assay were performed to examine the properties of co-cultured spheroids. Periodontal tissue defects were prepared in the maxillary first molars of rats and subjected to transplantation assay. RESULTS: The expression levels of stemness markers, vascular endothelial growth factor (VEGF), osteogenesis-related genes were up-regulated in co-cultured spheroids, compared with monolayer and spheroid-cultured hPDLMSCs. The nodule formation was also increased in co-cultured spheroids, compared with monolayer and spheroid cultures of hPDLMSCs. Treatment with co-cultured spheroids enhanced new cementum formation after 4 or 8 weeks of transplantation, although there was no significant difference in the new bone formation between co-cultured spheroids and hPDLMSC spheroids. CONCLUSIONS: We found that co-cultured spheroids enhance the periodontal tissue regeneration. Co-cultured spheroids of hPDLMSCs and HUVECs may be a useful therapy that can induce periodontal tissue regeneration.